Solitary intramuscular cysticercosis involving the triceps muscle a case Report - Vikas Chennamaneni (International Journal of Medical Research and Review, 2013)
Intramuscular cysticercosis is a less common presentation and high resolution ultrasound can help in clinching the diagnosis and avoiding unnecessary interventions. Patient can be managed conservatively with antihelminths and steroids.We present the case of a 23-year-old man with a swellingon theposterior side of right arm and was diagnosed as intramuscularcysticercosis in the triceps muscle on high-resolution ultrasound and managed conservatively with antihelminths.